2016
DOI: 10.1155/2016/6190285
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Research on Mongolian Medical Warm Acupuncture in Treating Insomnia

Abstract: Objective. Insomnia is one of the most common sleep disorders. Hypnotics have poor long-term efficacy. Mongolian medical warm acupuncture has significant efficacy in treating insomnia. The paper evaluates the role of Mongolian medical warm acupuncture in treating insomnia by investigating the Mongolian medicine syndromes and conditions, Pittsburgh sleep quality index, and polysomnography indexes. Method. The patients were diagnosed in accordance with International Classification of Sleep Disorders (ICSD-2). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Many studies have shown that the HPA is closely associated with the sleep rules [23][24][25]. Research indicates that exogenous CRH can increase the electroencephalogram frequency, light sleep, The Mongolian medical warm acupuncture group was able to increase the expression of the BLC-2 protein in the hippocampus.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have shown that the HPA is closely associated with the sleep rules [23][24][25]. Research indicates that exogenous CRH can increase the electroencephalogram frequency, light sleep, The Mongolian medical warm acupuncture group was able to increase the expression of the BLC-2 protein in the hippocampus.…”
Section: Discussionmentioning
confidence: 95%
“…It is a good choice for insomnia patients. There are many clinical reports on the treatment of insomnia with Mongolian medical warm acupuncture ( 16 ). The Mongolian medical warm acupuncture therapy is used in all of these clinical reports.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, acupuncture is commonly employed for handling mental wellness problems. Especially, many systematic reviews [ 7 , 14 , 15 ] and clinical randomized trials [ 16 , 17 ] indicated that acupuncture could be effective against insomnia. Additionally, numerous studies have found that acupuncture can alter the composition of the gut microbiota [ 18 – 20 ].…”
Section: Introductionmentioning
confidence: 99%